Реальные и мифические народы в изображениях на памятниках искусства из античных городов Северного Причерноморья (VI-IV вв. до н. э.) - Скржинская, М.В. (Боспорские исследования, 2009)
Foreigners on the antique monuments from the north Pontic area cities are included in the scenes illustrating literature and folklore creations. They were the characters who fought against Hellenoi or their contemporaries dwelling at the world’s end in the old days. Scythians, Ethiopians and Amazons belonged to the first; Arymaspians, Amazons and pygmies belonged to the second ones. Citizens of the North Pontic area states ranked unknown nations, e.g. Negroes, with imaginary Amazons and pygmies. There are almost no representations of well known barbarians; figures of Persians and Thracians are rare; images of Scythians are not numerous. The latter appeared in archaic period predominantly, when the legend of their participation in the Trojan War was popular. Representations of Libya people can be singled out in a separate group. They played a cognitive role for the majority of the north Pontic area population being one of a few knowledge sources about Africa.